Meta-Analysis of Outcomes After Intravascular Ultrasound–Guided Versus Angiography-Guided Drug-Eluting Stent Implantation in 26,503 Patients Enrolled in Three Randomized Trials and 14 Observational Studies - Ahn, Jung-Min; Kang, Soo-Jin; Yoon, Sung-Han; Park, Hyun Woo; Kang, Seung Mo; Lee, Jong-Young; Lee, Seung-Whan; Kim, Young-Hak; Lee, Cheol Whan; Park, Seong-Wook; Mintz, Gary S.; Park, Seung-Jung (The American journal of cardiology, 2014)
There are conflicting data regarding the benefit of intravascular ultrasound (IVUS)–guided percutaneous coronary intervention (PCI) over angiography-guided PCI. Since the last meta-analysis was published, several new studies have been reported. We performed a comprehensive meta-analysis to evaluate the clinical impact of IVUS-guided PCI with drug-eluting stent compared with conventional angiography-guided PCI. This meta-analysis included 26,503 patients from 3 randomized and 14 observational studies; 12,499 patients underwent IVUS-guided PCI and 14,004 underwent angiography-guided PCI. Main outcome measures were total mortality, myocardial infarction (MI), stent thrombosis, and target lesion revascularization (TLR). IVUS-guided PCI was significantly associated with more stents, longer stents, and larger stents. Regarding clinical outcomes, IVUS-guided PCI was associated with a significantly lower risk of TLR (odds ratio [OR] 0.81, 95% confidence interval [CI] 0.66 to 1.00, p = 0.046). In addition, the risk of death (OR 0.61, 95% CI 0.48 to 0.79, p <0.001), MI (OR 0.57, 95% CI 0.44 to 0.75, p <0.001), and stent thrombosis (OR 0.59, 95% CI 0.47 to 0.75, p <0.001) were also decreased. In conclusion, our meta-analysis demonstrated that IVUS-guided PCI was associated with lower risk of death, MI, TLR, and stent thrombosis after drug-eluting stent implantation.